Atrial Fibrillation, Neurocognitive Decline and Gene Expression After Cardiopulmonary Bypass - Dalal,Rahul S. (2015)
ABSTRACT OBJECTIVE: Atrial fibrillation and neurocognitive decline are common complications after cardiopulmonary bypass. By utilizing genomic microarrays we investigate whether gene expression is associated with postoperative atrial fibrillation and neurocognitive decline. METHODS: Twenty one cardiac surgery patients were prospectively matched and underwent neurocognitive assessments pre-operatively and four days postoperatively. The whole blood collected in the pre-cardiopulmonary bypass, 6 hours after-cardiopulmonary bypass, and on the 4th postoperative day was hybridized to Affymetrix Gene Chip U133 Plus 2.0 Microarrays. Gene expression in patients who developed postoperative atrial fibrillation and neurocognitive decline (n=6; POAF+NCD) was compared with gene expression in patients with postoperative atrial fibrillation and normal cognitive function (n=5; POAF+NORM) and patients with sinus rhythm and normal cognitive function (n=10; SR+NORM). Regulated genes were identified using JMP Genomics 4.0 with a false discovery rate of 0.05 and fold change of >1.5 or <-1.5. RESULTS: Eleven patients developed postoperative atrial fibrillation. Six of these also developed neurocognitive decline. Of the 12 patients with sinus rhythm, only 2 developed neurocognitive decline. POAF+NCD patients had unique regulation of 17 named genes preoperatively, 60 named genes six hours after cardiopulmonary bypass, and 34 named genes four days postoperatively (P<0.05) compared with normal patients. Pathway analysis demonstrated that these genes are involved in cell death, inflammation, cardiac remodeling and nervous system function. CONCLUSION: Patients who developed postoperative atrial fibrillation and neurocognitive decline after cardiopulmonary bypass may have differential genomic responses compared to normal patients and patients with only postoperative atrial fibrillation, suggesting common pathophysiology for these conditions. Further exploration of these genes may provide insight into the etiology and improvements of these morbid outcomes.